Review on retention of long-chain omega-3 polyunsaturated fatty acids EPA and DHA in fish as affected by cooking methods - Muhammad Alinafiah, Suryati; Azlan, Azrina; Amin, Ismail; Mahmud Ab Rashid, Nor-Khaizura (Universiti Putra Malaysia, 2022)
Fatty acids are essential building blocks for the structural components of the cells, tissues, organs, and certain biologically active substances synthesis. Omega-3 polyunsaturated fatty acids are long-chain fatty acids essential for several biological functions including oxidative stress reduction and cardiovascular safety. Diet rich in omega-3 fatty acids is well acknowledged as beneficial to one's health and well-being. For the development of balanced diets, the nutrient content of raw and cooked foods is crucial. However, cooking method, animal age, and carcass characteristics might affect nutrient retention during cooking, and these factors are often unique to specific countries. This review thus provides a general overview of several cooking effects on long-chain omega-3 retention in fish. It can be concluded that the DHA and EPA's true retention values are correlated to the impact of different cooking treatments.